Book review of ‘Network services: QoS, Signalling, Processes’ by Harry Perros - Warfield, Bob (Journal of Telecommunications and the Digital Economy, 2020)
This article reviews Networking Services: QoS, Signalling, Processes [Amazon Digital Services: ASIN BooIJFZTWC], by Harry Perros, Computer Science Department, North Carolina State University, USA; 2014, 516 pp.